2005
DOI: 10.1093/bja/aei224
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electrical velocimetry and transoesophageal Doppler echocardiography for measuring stroke volume and cardiac output † †Declaration of interest. This study was supported by Osypka Medical GmbH, Berlin, Germany.

Abstract: The agreement between EV-CO and TOE-CO is clinically acceptable, and these two techniques can be used interchangeably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 25 publications
(26 reference statements)
4
69
1
Order By: Relevance
“…Our findings are in accordance with the results of other studies: Schmidt et al [16] described the interchangeability of EV and transoesophageal aortic Doppler in a homogenous cohort of 37 patients undergoing coronary surgery. Suttner et al [17] reported good correlation and acceptable agreement between EV and pulmonary artery thermodilution in adult patients after cardiac surgery.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in accordance with the results of other studies: Schmidt et al [16] described the interchangeability of EV and transoesophageal aortic Doppler in a homogenous cohort of 37 patients undergoing coronary surgery. Suttner et al [17] reported good correlation and acceptable agreement between EV and pulmonary artery thermodilution in adult patients after cardiac surgery.…”
Section: Discussionsupporting
confidence: 93%
“…(1.018 9 SV TTE ), i.e. near the line of identity, thus highlighting the good predictability for the two methods, albeit a little less well than that found by Schmidt et al [16] and Norozi et al [18].…”
Section: Methods Comparisonmentioning
confidence: 63%
See 1 more Smart Citation
“…As a result, there is a continuing search for a method of CO measurement that is less invasive than its predecessors. In this respect, impedance cardiography, which calculates SV and CO from changes in the instantaneous mean resistance (i.e., impedance) of a small electrical current transferred through the body, has received much attention in the last four decades because it is noninvasive, easy to use, and adapted for continuous monitoring of CO and related parameters (16).…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm used is thought to be unaffected by changes in low conductivity compartments such as lung and in theory should be more accurate than bioimpedance. The technique has compared well to trans-oesophageal echocardiography [90], and bolus thermodilution with the pulmonary artery catheter [91].…”
Section: Electrical Velocimetrymentioning
confidence: 99%